Implicit Bias Training Standards in Health Care: Did Michigan Get It Right? A Policy and Ethical Framework Analysis. - Gailliard, Megan; Fogarty, Kieran; Lagerwey, Mary (Open Journal of Occupational Therapy (OJOT))
In 2022, Michigan joined a handful of states requiring implicit bias training for its health care professionals. In its ideal application, implicit bias training of health care professionals will result in a reduction of the implicit biases held by health care providers. This bias reduction will, in theory, contribute to improved equity in the delivery of health care services. Ultimately, the less biased health professional, now delivering health care services with a more equitable hand, will help reduce health disparities in the State of Michigan. This analysis of Mich. Admin. Code R.338.7004 - Implicit bias training standards for licensed and registered health care professionals, examines the policy's origin, intent, foundational principles, and implementation. Implicit bias training of health care professionals has been mandated state-wide to improve health equity; however, lack of evidence-based structure and administration threatens to defeat the stated objectives of Michigan's implicit bias training policy. Potential for the generation of large-scale data to better inform implicit bias training is a missed opportunity without policy revision. Recommendations for high-priority revisions to the policy are provided as a guide for Michigan lawmakers to 'get it right' by delivering an implicit bias training initiative that is data generating and evidence-based.